Problem of universals of Christianities and differentia specifica of its life are in history (Part IIІ - From Byzantium to Rus: evolution controversy) - Ihor Pasko (Cхід, 2013)
In the third part of the essay author focuses on the conceptual differences between the Byzantine Christian orthodoxy and a new pattern, which gradually formed on the northeastern outskirts of Europe.